1989
DOI: 10.3109/01485018908986783
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Mammalian Sperm Motility

Abstract: The physiological regulation of sperm motility has become more amenable to investigation since the demonstration that CAMP and calcium play a role in modulating the functioning of the flagellar axoneme. Although the external triggering mechanisms that initiate motility and capacitation are still unknown, evidence supports a modification of the calcium balance by gated Ca2+ channels, accompanied by shifts in the internal pH. Ca2' and pH may in turn act indirectly through CAMP and CAMPdependent kinase (kinase,) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(65 citation statements)
references
References 136 publications
1
61
0
3
Order By: Relevance
“…It has been suggested that the microtubules play the major role in sperm motility [22]. Because Rho proteins are apparently not involved in the regulation of the microtubule system [3,7,23] our data extend the current concept of flagellar motility.…”
Section: Resultssupporting
confidence: 76%
“…It has been suggested that the microtubules play the major role in sperm motility [22]. Because Rho proteins are apparently not involved in the regulation of the microtubule system [3,7,23] our data extend the current concept of flagellar motility.…”
Section: Resultssupporting
confidence: 76%
“…First, demembranated fowl spermatozoa can be motile even in the presence of millimolar concentrations of Ca 2C (Ashizawa et al 1989), whereas such high concentrations of Ca 2C inhibit the motility of demembranated mammalian spermatozoa (White & Voglmayer 1986, Feng et al 1988. Secondly, cAMP is indispensable for the initiation and stimulation of flagellar motility of mammalian spermatozoa (for a review, see Tash & Means 1983, Lindemann & Kanous 1989), but is not necessary for fowl spermatozoa, especially at 40 8C (Ashizawa et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This alkalinization activates the dynein ATPase needed for sperm swimming. This pH change also activates SUsAC [23], increasing cAMP levels, which in turn activates PKA to phosphorylate axonemal proteins needed for initiation and maintenance of sperm motility [9,34,[58][59][60][61][62][63][64].…”
Section: Susac and Protein Phosphorylationmentioning
confidence: 99%